Pengaruh Minat Menggunakan Layanan Internet Banking PT. Haldin Pacific Semesta Dalam Bertransaksi Bisnis - Sari Hartini; Meilina Rahayu (Universitas Bina Sarana Informatika, 2018)
This study aims to investigate the effect of internet banking usage and utilization on business transaction satisfaction at PT Haldin Pacific Semesta. In this study the authors used a questionnaire to collect information from respondents. The number of respondents is 50 respondents. In the selection of respondents selected at random or random. The test instrument used is the quantitative method and multiple linear regression. The results obtained are that the use and use of internet banking in PT Haldin Pacific Semesta have a significant effect on the satisfaction of business transactions. The test results show that the satisfaction of business transactions using internet banking is 59.50% means 40.50% influenced by other variables that are not in the scope of the author's research.